SISTEM INFORMASI ABSENSI KARYAWAN BERBASIS WEB PADA APM LOGISTICS - rusli, mulyadi; Mubarok, Husni (LP2M Universitas Nurdin Hamzah, 2024)
The Timestamp Camera application has a time deficiency that can be set as desired by the user. Therefore, employees can still cheat on attendance by setting the time on their Smartphone. This is considered ineffective. Because the data must be sent to the HRD team. Because managing employee attendance data is a big responsibility. If there is fraud on employees, it will affect the results of the data summary. Because specifically for couriers it will have an impact on the selection of the best courier candidates.